Expertise and its contribution to the notion of protective factors in offender rehabilitation and desistance. (January 2017) - Nee, Claire; Vernham, Zarah
Abstract: In the field of offender corrections, a preoccupation with risk prediction has come at the expense of explanation, and an overemphasis on risk factors has come at the expense of understanding protective factors. Some strides have been made in describing and categorising the types of factors that protect young people from a life of crime, or promote competencies and potentials that help them avoid it altogether. We argue, however, that like the field of dynamic risk factors, we know very little about the nature and function of these features, beyond describing them. The article describes theory and research associated with expertise and its qualities and value as both a risk and a protective factor in the prevention of crime. It draws from literature in forensic psychology, criminology, resilience and neuroscience.